Membangun Karakter Islami melalui Desain Pembelajaran Digital - Nurul Izzah Yasmin; Muhammad Taufiq; Gusmaneli Gusmaneli (Lembaga Pengembangan Kinerja Dosen, 2024)
Digital learning design has great potential in shaping students' Islamic character in this digital era. However, its implementation faces several challenges, such as limited access to technology, difficulties in internalizing Islamic values through digital media, and a reduction in the essential social interaction required for character development. Additionally, distractions from technology, the limited availability of relevant Islamic content, and the lack of technological skills among teachers also pose significant barriers. To overcome these challenges, solutions are needed, including the improvement of technology infrastructure, the development of more relevant Islamic learning content, and teacher training in effective technology usage. Approaches that involve social interaction, digital skills development, and holistic character evaluation can enhance the effectiveness of digital learning in building Islamic character. Therefore, digital learning can serve as an effective tool for educating students with Islamic values, provided it is balanced with the right approach.